Two decades of HIV/AIDS mortality trend analysis in the Philippines - Balt, Arafat M.; Mangotara, Rosnia D.; Sambawa, Nihaya G.; Alamada, Princess Altheya Mae P.; Demayo, Chin-chin J.; Demayo, Cesar G. (International Journal of Public Health Science (IJPHS), 2025)
Public health surveillance indicates that the country's HIV infection rate is rising, with the Western Pacific region experiencing the highest growth. Due to the scarcity of studies on HIV in the nation, the present state of the HIV epidemic must be ascertained by gathering data from public health surveillance and HIV mortality time trend analysis. The Department of Health's Philippine Health Statistics (PHS) provided the information. The PHS-recommended algorithms for vital health indicators were used to calculate mortality rates. According to the study's findings, the death rate in the nation is rising, necessitating tight efforts to stop the virus's transmission and provide access to anti-retroviral therapy. Although there is a considerable difference between the two sexes, men had a greater mortality rate than women, suggesting that men were more vulnerable to HIV/AIDS mortality. The study also revealed that HIV testing hurdles were to blame for making young to middle-aged individuals the population most susceptible to mortality from this illness. Additionally, the National Capital Region has the most significant mortality rate, so the government should focus on promoting health in this area as it has the highest mortality rate.